Association between early childhood caries and parental educational status among children in Ile-Ife, Nigeria - Foláyan, Moréniké Oluwátóyìn; Zuñiga, Roberto Ariel Abeldaño; Mohebbi, Simin Z.; Khami, Mohammad R. (Frontiers in Oral Health, 2025)
BackgroundParental educational status is a known risk factor for early childhood caries (ECC). This study explores the association between parental educational status and ECC prevalence among children aged 0–5 years in Ile-Ife, Nigeria, using the Sustainable Development Goal 4 (SDG 4) framework.MethodsA cross-sectional household survey was conducted between December 2024 and January 2025, involving 1,339 mother–child pairs. Data were collected through structured questionnaires, capturing confounding variables (child's age and sex at birth; infant-feeding profile, such as age at introduction of sugar into the meal; and oral health behavior, such as toothbrushing frequency, use of fluoridated toothpaste, and consumption of refined carbohydrates between meals); independent variable (parental education levels categorized as Qur'anic/primary, secondary, or tertiary); and the dependent variable (ECC determined by the use of the dmft index). A multivariable logistic regression analysis was conducted to determine the associations between the independent and confounding variables and between the independent and dependent variables after adjusting for confounding variables.ResultsThe ECC prevalence was 7.3%, with the highest rate observed in children 60–71 months (12.6%). While maternal and paternal education levels showed no direct association with ECC prevalence, they were indirectly linked to ECC through behavioral pathways. Higher maternal education was associated with greater toothbrushing frequency, showing increased odds for both secondary (OR = 3.411, p = 0.037) and tertiary education levels (OR = 5.109, p = 0.009). However, it was also linked to higher consumption of refined carbohydrates, with secondary (OR = 0.336, p = 0.002) and tertiary education (OR = 0.362, p = 0.011) showing lower odds of limited intake. Similarly, higher paternal education was positively associated with the use of fluoridated toothpaste—secondary (OR = 2.417, p = 0.003) and tertiary (OR = 3.013, p = 0.001)—but also corresponded with increased refined carbohydrate consumption (secondary: OR = 0.329, p = 0.046).ConclusionThese findings indicate that while education promotes some protective behaviors, it may also contribute to increased dietary risks mediated by environmental and socioeconomic factors. Context-specific actions are required to align the SDG 4 with efforts to reduce ECC prevalence in vulnerable populations.